Diversificação cariotípica no gênero Astyanax (Characidae) com enfoque na citotaxonomia do grupo - Tenório, Renata Cristina Claudino de Oliveira (2012)
Astyanax is a very diverse group of neo-tropical fish, whose different forms take the most diverse environments. That great diversity of forms is also reflected in some cytogenetic and/or molecular aspects that have been repeatedly demonstrated by the classic cytogenetic techniques or with the use of DNA molecular markers. Aiming at analyze and characterize some species of that gender that inhabit in some streams of Cerrado of Mato Grosso, six species of Astyanax argyrimarginatus, A. elachylepis, A. xavante, A. altiparanae gender were studied and two new species of A. aff. bimaculatus e A. sp. were named provisionally in this research. For A. aff. bimaculatus four populations were analyzed. For a better comparison in the karyotypic data A. altiparanae was also analyzed, a common species in Alto Paraná Basin, it was also studied by several research groups. In order to accomplish a detailed cytogenetic study, based on the use of base-specific fluorochromes and ribosomal genes mapping a technique named FISH, in the sense of understanding some mechanisms associated with the establishment of those species. The results revealed 2n=50 Chromosomes for all A. aff bimaculatus species and populations, with the exceptions of Astyanax sp. Which has a karyotype with 52 chromosomes that represents a novelty for the group. Small variations in the karyotypes macrostructure were identified, however, those were pretty relevant when analyzed based on the classic chromosomal banding methodologies with fluorochromes and FISH. Those obtain results for Astyanax showed great karyotype diversity when comparing the cytogenetic data available for other populations. That information indicated the need of a wide review in the set of individuals here referred to as A. aff. bimaculatus and for description purposes of Astyanax sp., including the possibility of suggesting the insertion of that species in a Astyanax. separate gender.